2002
DOI: 10.1097/00003226-200208000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiological Features and Laboratory Results of Fungal Keratitis

Abstract: To the best of our knowledge, this review presents the epidemiological features and laboratory results of the largest series of fungal keratitis ever reported in the literature. Keratomycosis is predominant in young adults with trauma as the major predisposing factor. With fungal keratitis being a major ophthalmologic problem in the tropical regions of the world, data available on the epidemiological features of a large series would greatly help medical practitioners at primary and secondary health care center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(119 citation statements)
references
References 21 publications
7
111
1
Order By: Relevance
“…14 Two separate studies in South India have found the microbial keratitis to affect men more than women. 3,17 In this study, 66% of the participants were men. Male patients may be more likely to be agricultural workers or involved in outdoor activities, placing them at higher risk of trauma or injury to the cornea.…”
Section: Discussionmentioning
confidence: 74%
“…14 Two separate studies in South India have found the microbial keratitis to affect men more than women. 3,17 In this study, 66% of the participants were men. Male patients may be more likely to be agricultural workers or involved in outdoor activities, placing them at higher risk of trauma or injury to the cornea.…”
Section: Discussionmentioning
confidence: 74%
“…5 Other predisposing factors include corneal surgery, prolonged use of corticosteroids or antibiotics, pre-existing ocular diseases, systemic diseases such as diabetes mellitus, and contact lenses. 3,4,6,7 Fungi produce a slowly progressive disease characterized by localized infiltrate. Classical clinical features are shown in Figures 1a and b.…”
Section: Keratitismentioning
confidence: 99%
“…25 In the present study the most common fungal isolate is Fusarium spp (30.43), followed by Aspergillus spp (26.09%), Rhizopus spp (17.39%), Mucor spp, Alternaria spp, and unidentified filamentous fungi 8.70% each.…”
Section: Discussionmentioning
confidence: 51%
“…In a study by Gopinathan U et al 25 KOH was positive in 91.0% of 95.4% fungal isolates, study by Sharma S et al 26 the sensitivity & specificity of fungal detection was 81.2% & 83.8% respectively. In another study by Sharma S et al 27 the sensitivity & specificity of fungal detection in early and late keratitis was 61.1% & 99.0% and 87.1% & 83.7% respectively.…”
Section: Discussionmentioning
confidence: 92%